Analisis Beban Kerja Mental Pekerja Menggunakan Metode Nasa TLX di PT Aneka Jasa Sorwako - Muhammad Irgi Fachrezy; Andung Jati Nugroho (Jurnal Cakrawala Akademika, 2025)
In making mine roads, workers carry out work in conditions that are less comfortable carrying out work activities for long periods of time. For example, surveyors carry out their activities from morning to evening in hot or rainy weather conditions and require little time. Supervise the control of work so that it complies with the directions and time that has been determined. In carrying out these activities, high energy and precision is required, resulting in mental and physical workload. By carrying out this research, an evaluation of mental workload will be carried out to find out how much mental workload is felt by workers in carrying out work activities and what load factors most influence workers' mental workload. The analysis was carried out using the NASA-TLX method to identify the mental workload experienced by workers. The results of data processing show that the section that has the highest workload is the supervisory section with an average of 81.1, then the operator section with an average value of 80.9, and the lowest is the survey section with an average value of 80. In the shift comparison The workload for operators on the morning shift has a total score of 822, while on the night shift the total score is 796. Then on the morning shift the supervisor has a higher workload with a total score of 335, while on the night shift the total score is 314. So it can be seen that the workload during the shift morning shift is greater than the night shift.